2018
DOI: 10.21833/ijaas.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

The impact of supply chain collaboration on operational performance: Empirical evidence from manufacturing of Malaysia

Abstract: Indeed due to global advancement, rapid technological innovation, and enhancing regional influence, supply chain (SC) has become an essential element. Now, competition has shifted from organization to industry level; any disruption can not only disturb organization but also effect whole industry. Although Malaysia is known from palm oil and rubber but manufacturing sector has highest growth rate (7.1%) and second contributor to GDP and employer. Due to regional and economic shift toward China and India this se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 29 publications
3
32
0
1
Order By: Relevance
“…Logistics uncertainty is viewed as an uncertainty factor that causes a delay or an interruption originating from own or partners logistics system or natural disasters throughout the logistic process (Tse et al, 2016). Logistic side risks are considered, the material flow of goods from the supply side and to demand side, usually, little attention has been paid for logistic Although, it has been noted that logistic disruption is ''quickly cripple the entire supply chain'' (Punniyamoorthy et al, 2013;Shahbaz, Rasi, Ahmad & Sohu, 2018). Normally, logistic side risks originates from cargo damage, supply side constrictions or warehouse problem (Wilson, 2007), Delay in delivery (Wang, Jie & Abareshi, 2014), improper packaging (Zubair & Mufti, 2015), labor disputes, natural disasters, terrorist activities, and transportation infrastructure failures (Thun & Hoenig, 2011), Wrong Choice of mode of transportation (Punniyamoorthy et al, 2013), transportation complexity (Wagner & Neshat, 2012).…”
Section: Logistic Side Risksmentioning
confidence: 99%
“…Logistics uncertainty is viewed as an uncertainty factor that causes a delay or an interruption originating from own or partners logistics system or natural disasters throughout the logistic process (Tse et al, 2016). Logistic side risks are considered, the material flow of goods from the supply side and to demand side, usually, little attention has been paid for logistic Although, it has been noted that logistic disruption is ''quickly cripple the entire supply chain'' (Punniyamoorthy et al, 2013;Shahbaz, Rasi, Ahmad & Sohu, 2018). Normally, logistic side risks originates from cargo damage, supply side constrictions or warehouse problem (Wilson, 2007), Delay in delivery (Wang, Jie & Abareshi, 2014), improper packaging (Zubair & Mufti, 2015), labor disputes, natural disasters, terrorist activities, and transportation infrastructure failures (Thun & Hoenig, 2011), Wrong Choice of mode of transportation (Punniyamoorthy et al, 2013), transportation complexity (Wagner & Neshat, 2012).…”
Section: Logistic Side Risksmentioning
confidence: 99%
“…Table 2 shows the measurement items for collaboration adopted from [15]. Shahbaz et al [28] shown, after a comprehensive literature review, that further analysis of supply chain risk management was needed and designates three important gaps. Conferring to him, there is a lack of integration between the internal and external aspects of the SC.…”
Section: Collaborationmentioning
confidence: 99%
“…Logistic side risks are considered, material flow of goods from the supply side and to demand side, usually, little attention has been paid for the logistic side. Although, it has been noted that logistic disruption is ''quickly cripple the entire supply chain'' (Punniyamoorthy et al, 2013;Shahbaz et al, 2018a). Normally, logistic side risks originate from cargo damage, supply side or warehouse problem (Wilson, 2007), delay in delivery (Wang et al, 2014), improper packaging (Zubair and Mufti, 2015), labor disputes, natural disasters, terrorist activities, and transportation infrastructure failures (Thun and Hoenig, 2011), wrong choice of mode of transportation (Punniyamoorthy et al, 2013), transportation complexity (Wagner and Neshat, 2012).…”
Section: Logistic Side Risksmentioning
confidence: 99%